2018
DOI: 10.5897/jhf2018.0532
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of potato (Solanum tuberosum L.) cultivars as influenced by plant spacing at Haramaya and Hirna, Eastern Ethiopia

Abstract: ) and the same variety also produced the maximum total tuber yields at both locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
0
0
Order By: Relevance
“…This result agree with on fresh tuber yield was obtained in Iraq 35.23 ton/ha in furrow irrigation [24]. And also, Birhanu [25] reported 56.85 ton/ha and 39.08 ton/ha fresh potato tuber yield observed in Hirna and Haramaya respectively in 2013, during the main season.…”
Section: Effect Of Water Level On Tuber Yield and Crop Water Producti...supporting
confidence: 90%
“…This result agree with on fresh tuber yield was obtained in Iraq 35.23 ton/ha in furrow irrigation [24]. And also, Birhanu [25] reported 56.85 ton/ha and 39.08 ton/ha fresh potato tuber yield observed in Hirna and Haramaya respectively in 2013, during the main season.…”
Section: Effect Of Water Level On Tuber Yield and Crop Water Producti...supporting
confidence: 90%
“…This may be due to that under wider spacing and whole tuber planting there was proper growth and development of the plant resulting in more yield of large-size tubers which ultimately increases the marketable yield, total yield as well and biological yield, while under closer spacing using cut tubers, there was higher plant population per unit area which increases the yield of all of the size tuber. The present finding also confirmed the results of Malik et al and Birhanu et al [15,11] who reported that the tuber yield per hectare was higher with whole tubers planting as compared to cut tubers under the same plant spacing.…”
Section: Plant Spacingsupporting
confidence: 93%
“…The varietal difference in potato varieties concerning tuber yield, marketable yield as well and biological yield was also noticed by Yadav et al [16]. The present findings are following results reported by Abrha et al [17], Lal et al [18] and Birhanu et al [11]. The interaction effect between different plant spacings and potato varieties was found non-significant for tuber yield, marketable yield as well and biological yield.…”
Section: Plant Spacingsupporting
confidence: 89%
See 1 more Smart Citation